2009
DOI: 10.1037/a0014699
|View full text |Cite
|
Sign up to set email alerts
|

Effect sizes for growth-modeling analysis for controlled clinical trials in the same metric as for classical analysis.

Abstract: The use of growth-modeling analysis (GMA)--including Hierarchical Linear Models, Latent Growth Models, and General Estimating Equations--to evaluate interventions in psychology, psychiatry, and prevention science has grown rapidly over the last decade. However, an effect size associated with the difference between the trajectories of the intervention and control groups that captures the treatment effect is rarely reported. This article first reviews two classes of formulas for effect sizes associated with clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
622
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 746 publications
(628 citation statements)
references
References 58 publications
3
622
1
2
Order By: Relevance
“…5 We also examined effects of prosocial and self-focused behavior on each subcomponent of psychological flourishing (psychological well-being, social well-being, and emotional well-being). We found that prosocial behavior led to greater linear and quadratic changes in psychological well-being relative to self-focused behavior (linear: ␥ 11 ϭ 0.11, SE ϭ 0.06, t (733) (Feingold, 2009). This effect size represents the magnitude of the difference in average growth rates between the two conditions.…”
Section: Changes In Psychological Flourishingmentioning
confidence: 83%
“…5 We also examined effects of prosocial and self-focused behavior on each subcomponent of psychological flourishing (psychological well-being, social well-being, and emotional well-being). We found that prosocial behavior led to greater linear and quadratic changes in psychological well-being relative to self-focused behavior (linear: ␥ 11 ϭ 0.11, SE ϭ 0.06, t (733) (Feingold, 2009). This effect size represents the magnitude of the difference in average growth rates between the two conditions.…”
Section: Changes In Psychological Flourishingmentioning
confidence: 83%
“…Despite increasing over time, the level of CR of the control improvers remained below the 50th percentile of the baseline CR of the entire cohort. (Feingold, 2009 (Feingold, 2009 …”
Section: Discussionmentioning
confidence: 99%
“…Future research is planned to determine whether this increase in cognitive reserve is sufficient to offset age-related cognitive decline and further, whether this increase in CR mitigates the risk for degenerative conditions such as dementia, or delays the onset of clinical symptoms of dementia in those at risk of dementia. (Feingold, 2009) …”
Section: Discussionmentioning
confidence: 99%